The importance of clear margins in myxofibrosarcoma: Improving local control by means of staged resection and reconstruction. Issue 10 (October 2021) - Berner, Juan Enrique; Crowley, Timothy P.; Teelucksingh, Sachin; Lee, Daniela; Ghosh, Kanishka M.; Beckingsale, Thomas B.; Rankin, Kenneth S.; Ragbir, Maniram
Abstract: Introduction: Myxofibrosarcomas are associated with a locally infiltrative growth pattern, making a clear-margin resection margin challenging. This leads to high local recurrence rates. While immediate wound closure and adjuvant radiotherapy has been proposed to mitigate incomplete excisions, we present our experience treating myxofibrosarcomas with staged excisions until clear margins are obtained, prior to reconstruction. Methods: All patients with myxofibrosarcomas treated with a curative intent at our centre between 2009 and 2019 were identified. Patient demographics, tumour characteristics, number of resections, method of reconstruction, adjuvant therapy, complications, local recurrence rates, length of hospital stay and overall survival were assessed. Results: 97 consecutive eligible patients were identified. Forty-six (47%) had positive margins reported following a first resection. The median number of resections required to obtain clear margins was two and the median time from first excision to definitive wound closure was 15 days. Local recurrence rate for the whole cohort was 14%. Patients who had staged resection until clear margins were obtained had a significantly lower rate of local recurrence compared to those who had positive margins at time of reconstruction (p-value = 0.001). The estimated 5-year disease-specific survival for the whole cohort was 93%. Discussion: Obtaining clear margins in myxofibrosarcoma via staged resections was associated with lower local recurrence rates for patients who had an initial resection with positive margins. The outcomes of performing staged resections are equivalent to patients for whom a clear margin were obtained in the first instance.